Antimicrobial activity and chemical composition of white birch (Betula papyrifera Marshall) bark extracts. Issue 1 (3rd October 2019) - Blondeau, Dorian; St‐Pierre, Annabelle; Bourdeau, Nathalie; Bley, Julien; Lajeunesse, André; Desgagné‐Penix, Isabel
Abstract: Extracts from white birch have been reported to possess antimicrobial properties, but no study has linked the chemical composition of bark extract with antimicrobial activity. This study aimed to identify white birch ( Betula papyrifera Marshall) bark extracts with antimicrobial activity and elucidate its composition. In order to obtain the highest extraction yield, bark residues >3 mm were retained for extraction. A total of 10 extraction solvents were used to determine the extraction yield of each of them. Methanol and ethanol solvents extracted a greater proportion of molecules. When tested on eight microorganism species, the water extract proved to have the best antimicrobial potential followed by the methanol extract. The water extract inhibited all microorganisms at low concentration with minimal inhibitory concentration between 0.83 and 1.67 mg/ml. Using ultraperformance liquid chromatography coupled to a time‐of‐flight quadrupole mass spectrometer, several molecules that have already been studied for their antimicrobial properties were identified in water and methanol extracts. Catechol was identified as one of the dominant components in white birch bark water extract, and its antimicrobial activity has already been demonstrated, suggesting that catechol could be one of the main components contributing to the antimicrobial activity of this extract. Thus, extractives from forestry wastes have potential for new applications to valorize these residues. Abstract : We have shown that several extracts of white birch bark residues display natural antimicrobial activity. Among them, the water extract followed by the methanol extract proved to have the best antimicrobial potential. For the first time, extracts were characterized using ultrahigh‐performance liquid chromatography‐quadrupole time‐of‐flight mass spectrometry, which led to the identification of several molecules including catechol, predominant in the water extract, which is known to have antimicrobial activity.